Lonely Planet where to go when hiking : the ultimate month-by-month trip-planner for hikes, walks & treks - Baxter, Sarah; Bloomfield, Paul (Lonely Planet, 2026)
Get ready for the hike of a lifetime with this ultimate guide to a year's worth of amazing hiking experiences. Perfect for hikers of all skill levels looking for their next challenge in the great outdoors with ideas for multi-day walks and epic treks-from Spain's Camino Francés, California's high sierras on the John Muir Trail, South Africa's coastal Strandloper Trail and many more.